A repetição na psicanálise e suas repercussões clínica com o aporte do conceito de repetição em Kierkegaard - Barbosa Neto, Esperidião (2015)
The theme of repetition crosses the entire psychoanalytic theory, having become one of its fundamental concepts. Freud developed the concept of repetition from his clinical experience and Lacan placed the order of the Real. In the field of Philosophy, repetition was defined by the philosopher Kierkegaard, a Danish thinker of the nineteenth century. The psychoanalytic concept of repetition is distinct from philosophy; however, they are intertwined in some points. The psychoanalytic clinic is presented as a place of repetition and speech; therein, according to the articulation we made, the subject is also thought from the existence, according to Kierkegaard's conception. This research is of theoretical nature and uses clinical fragments; has as main objective to analyze the concept of repetition in psychoanalysis, with the contribution of Kierkegaardian concept of repetition, highlighting the clinical implications at the interface of the two concepts. The specific objectives are: to investigate the concept of repetition in Freud and Lacan; study the concept of repetition in Kierkegaard; situate the psychoanalytic clinic as a place of repetition and speech; highlight the creativity in the clinical process, considering the positivity of repetition from the point of view of Kierkegaard articulated with the Psychoanalysis. As theoretical reference we use the theories of Freud, Lacan and Kierkegaard. The text is presented in three chapters: in the first chapter, we work with the concept of repetition from the theoretical elaborations of Freud and Lacan's theoretical contribution; in the second chapter, we present the concept of repetition in Kierkegaard; in the third chapter, we situate the clinical implications of the psychoanalytic concept of repetition in the interface with the Kierkegaardian concept, considering the demand of the suffering in the subject‟s present context. In conclusion, we present a reflection on the subject as capable of developing an affective experience of trauma and all the excitement received as inheritance, to build something that belongs to him. We hope that the approach between psychoanalysis and Kierkegaard's philosophy contributes to a better understanding of the concept of repetition and, above all, enriches the clinical work.